PRODUCTIVITY ANALYSIS IN THE CONTEXT OF INTERNATIONAL TRADE FACILITATION: THE EXAMPLE OF TURKEY (Third Sector Social Economic Review, 2020)
The steps that should be taken in order to facilitate trade with policy implications which aim to increase the efficiency at every process of trade activities and to decrease trade costs have great importance for all countries in the World as well as for Turkey. This study aims to determine the level of trade facilitating regulations that will increase the competitiveness of Turkey in global markets through the international indexes whose purpose is to statethe trade facilitation levels of countries.  In this context the results of Logistic Performance Index (LPI), Information Technologies Development Index (IDI), Ease of Doing Business Index and Global Digital and Sustainable Trade Facilitation Survey are analyzed and the situation of Turkey on the way to facilitate trade is examined through the different aspects that each index targets to explore.
Keywords: Trade Facilitation; International Trade; Trade Facilitation Aggreement; Trade Facilitation Measures; Paperless Trade.